DESARROLLO DE UNA PÁGINA WEB PARA LA PROMOCIÓN DE LOS ATRACTIVOS TURÍSTICOS DEL CANTÓN MOCACHE, PROVINCIA DE LOS RÍOS - Hinostroza Fonseca, Ariana Tais (2024)
This present study was carried out in the Mocache canton located in the province of Los Ríos, currently recognized as "the hidden paradise", due to its high potential it seeks to promote and optimize the use of the various tourist attractions located in peaceful and conducive to rest. Through this initiative, it is intended to promote tourism in the Mocache canton, promoting its economic growth and strengthening its positioning as a destination. It is also a canton visited by national tourists due to its gastronomy and traditions, based mainly on products from the Ecuadorian coast. The general objective of this study is to develop a website to promote the tourist attractions of the canton. The proposal of this investigative work is to promote and disseminate the little-known and visited attractions of the Mocache canton to contribute to better tourism and economic development of the region.